The characteristics of mechanical engineering systems - Holmes, Roy, MSc (Pergamon international library of science, technology, engineering, and social studies., 1977)
The Characteristics of Mechanical Engineering Systems focuses on the characteristics that must be considered when designing a mechanical engineering system. Mechanical systems are presented on the basis of component input-output relationships, paying particular attention to lumped-parameter problems and the interrelationships between lumped components or """"black-boxes"""" in an engineering system. Electric motors and generators are treated in an elementary manner, and the principles involved are explained as far as possible from physical and qualitative reasoning. This book is comprised of